No time for smokescreen skepticism: A rejoinder to Shani and Arad. (April 2015) - Hall, C. Michael; Amelung, Bas; Cohen, Scott; Eijgelaar, Eke; Gössling, Stefan; Higham, James; Leemans, Rik; Peeters, Paul; Ram, Yael; Scott, Daniel; Aall, Carlo; Abegg, Bruno; et al.
Abstract: Shani and Arad (2014) claimed that tourism scholars tend to endorse the most pessimistic assessments regarding climate change, and that anthropogenic climate change was a "fashionable" and "highly controversial scientific topic". This brief rejoinder provides the balance that is missing from such climate change denial and skepticism studies on climate change and tourism. Recent research provides substantial evidence that reports on anthropogenic climate change are accurate, and that human-induced greenhouse gas emissions, including from the tourism industry, play a significant role in climate change. Some positive net effects may be experienced by some destinations in the short-term, but in the long-term all elements of the tourism system will be impacted. The expansion of tourism emissions at a rate greater than efficiency gains means that it is increasingly urgent that the tourism sector acknowledge, accept and respond to climate change. Debate on tourism-related adaptation and mitigation measures is to be encouraged and welcomed. Climate change denial is not. Highlights: Rejoinder to claims ofShani and Arad (2014) . Extent of scientific consensus on climate change indicated. Evidence for climate change is observational and predictive. Extent of tourism related emissions indicated. Concern of climate denial for scientific debate and communication.